Simple and Rapid Determination of Paracetamol in Oral Pharmaceutical Preparations by a Home-use Glucometer for Paediatric Subministration - Wang, Ge; Zhu, Jing; Wu, Wei; Zhang, Wei (Current Pharmaceutical Analysis, 2018)
Objective: A simple and rapid method for the measurement of paracetamol in oral pharmaceutical preparations by a commercial glucometer was proposed. Methods: The established method was successfully applied to the determination of paracetamol in oral solid preparations, and exhibited the excellent capability of resisting interference from co-existing excipients. The commercial disposable test strips of hand-held glucometer showed high consistency of electrocatalytic activity toward the oxidation of paracetamol between each other. Results: The linear range was from 0.2 mg/ml to 3.5 mg/ml with the detection limit of less than 0.2 mg/ml. The results demonstrated that the test strips can be used as a sensitive, selective and low-cost sensor for amperometric determination of paracetamol in oral solid dosage forms. Conclusion: The unique application of household glucometer presented a convenient home-use tool for the paediatric subministration of the home medicine in common use.
Keywords: Paediatric subministration